Green Synthesis of Near-Infrared Plasmonic Gold Nanostructures by Pomegranate Extract and Their Supramolecular Assembling with Chemo- and Photo-Therapeutics - Mimimorena Seggio; Francesca Laneri; Adriana C. E. Graziano; Marta Maria Natile; Aurore Fraix; Salvatore Sortino (Nanomaterials, 2022)
Au nanostructures exhibiting a localized surface plasmon resonance in the near-infrared spectral window are obtained in a single, green step at room temperature by pomegranate extract in the presence of a highly biocompatible β-cyclodextrin branched polymer, without the need of preformed seeds, external reducing and sacrificial agents, and conventional surfactants. The polymeric component makes the Au nanostructures dispersible in water, stable for weeks and permits their supramolecular assembling with the chemotherapeutic sorafenib and a nitric oxide (NO) photodonor (NOPD), chosen as representative for chemo- and photo-therapeutics. Irradiation of the plasmonic Au nanostructures in the therapeutic window with 808 nm laser light results in a good photothermal response, which (i) is not affected by the presence of either the chemo- or the phototherapeutic guests and (ii) does not lead to their photoinduced decomposition. Besides, irradiation of the hybrid Au nanoassembly with the highly biocompatible green light results in the NO release from the NOPD with efficiency similar to that observed for the free guest. Preliminary biological experiments against Hep-G2 hepatocarcinoma cell lines are also reported.